Intimate Wedding: The Transition of Gen Z Urban Marriage from Collective Celebration to Personal Space - Gadis Anastasia (Journal of Social and Policy Issues, 2026)
The rapid expansion of digital culture, shifting social values, and increasing economic considerations have reshaped how Generation Z perceives marriage, contributing to the growing preference for intimate weddings. This study aims to examine the factors influencing this preference, explore the psychological and cultural negotiation processes underlying the decision-making, and analyze the transformation of marriage rituals from the perspective of psychological anthropology. A qualitative case study approach was employed through digital document observation and a literature review. Data were collected from publicly accessible intimate wedding content on Instagram, TikTok, and YouTube and analyzed using thematic analysis. The findings indicate that the preference for intimate weddings emerges from the interaction of economic rationality, digital cultural influences, the pursuit of authenticity, and negotiations with family expectations, cultural norms, and broader social values. Through the practice of bricolage, Generation Z selectively preserves sacred elements of marriage while reconstructing ritual symbols to reflect contemporary identities and lifestyles. This study introduces the concept of reflexive ritual minimalism as a theoretical contribution, demonstrating that marriage rituals in the digital era are not diminished but symbolically reconfigured into more personal, reflective, and socially legitimate forms, thereby enriching psychological anthropology's understanding of ritual transformation in contemporary society